Memory and history: Oral techniques in the East African context - Gathogo, Julius M. (HTS teologiese studies, 2021)
Some historians have always erred in ignoring oral history methods, as it is always assumed wrongly that the only reliable and trustworthy source of history is the written word. The aim of this article is to underscore the nature and significance of oral histories, which rely on the memory of the narrators. In the case of both Ngugi wa Thiong’o’s and Wole Soyinka’s literary works, their respective childhood experiences are well captured, as they employ both the use of postcolonial and autobiography theories in their theoretical frameworks. In its methodology, this article relied heavily on extensive literature review, oral interviews and archival sources. In seeking to demonstrate the significance of oral history for the preservation of memory and for the writing of history in Africa, the author intends to build from both the above literary works and other theohistorical materials so as to convey the message that the methodology used in chronicling East African oral history, the history of Christian doctrines, Church history or social histories will require us to go beyond postcolonial theory and the theory of autobiography in order to harvest the rich and forward-moving historiographies that remain unexplored and/or unpublished altogether.Contribution: Memory as a critical tool that moves humanity forward is the main subject of this article. The article is relevant to the journal HTS Teologiese Studies/Theological Studies and the world of scholarship as it undertakes a multidisciplinary approach in engaging literary works with theo-historical works in order to build the case for oral techniques in modern scholarship.